DAUR HIDUP PRODUK DAN ALIH TEKNOLOGI: DEKONSTRUKSI INDUSTRI NASIONAL - Setyawan, Anton Agus (Universitas Muhammdaiyah Surakarta, 2000)
Technology becomes a major variable in the global industry. This phenomenon effects on the worlds economic structure due to the technological disparity between developed countries and developing ones. As a developing country, Indonesia faces the same problem with any other ones. The disparity could be analyze by correlating the global product life cycle and the technology transfer process. The conclussion is, technology transfer from developed countries to developing ones happens when the product mature and obsolence. To overcome this problem, Indonesia have to focus on a few points, which are: maintaining local knowledge, industrial deconstruction, intellectual capital enforcement and building the rich land and big people paradigm.